Heterosis studies in sunflower (Helianthus annuus L.): HETEROSIS STUDIES IN SUNFLOWER - S NEELIMA; K G PARAMESHWARAPPA (Journal of Oilseeds Research, 2013)
Thirty single cross sunflower (Helianthus annuus L.) hybrids produced were subjected to mid parent, better parent and standard heterosisstudies using three checks, viz., KBSH 1, KBSH 44 and GK 2002. The cross CMS 234 A x RHA-95-C-1 recorded the highest heterosis of 104.01% over better parent for seed yield which was followed by CMS 234 A x RHA-6D-1 and CMS 234 A x RHA-271 with 86.06 and 85.15%, respectively. None of the experimental hybrids could surpass the standard heterosis over checks KBSH-1 and GK 2002 for seed yield and oil content. However, three hybrids CMS 17 A x RHA-6D-1 (13.82), DCMS 51 A x R-298 (12.85), DCMS 51 A x RHA-272 (9.81) and 18 crosses where RHA-6D-1 and RHA-271 were used as male parents in combination with CMS 234 A, CMS 4546 A and DCMS 51 A showed significant heterosis over the check KBSH-44 for seed yield and oil content, respectively. The highest heterosis in the cross CMS 234 A x RHA-95-C-1 can be assigned to contribution of heterosis from component characters such as hull content, per cent seed filling and number of filled seeds/head.